Hierarchical Ag/Bi2MoO6 hollow nanoboxes with high photocatalytic performance. Issue 32 (19th July 2019) - Ma, Ying; Jia, Yulong; Lin, Yinhe; Shi, Wenbing
Abstract : Hierarchical Ag/Bi2 MoO6 hollow nanoboxes with high photocatalytic performance are fabricated by using Ag3 PO4 nanocubes as templates and Ag precursor sources. Abstract : Well-ordered hierarchical Ag/Bi2 MoO6 hollow nanoboxes are obtained through an artful hydrothermal method. Ag3 PO4 nanocubes serve as growth templates and precursor sources of Ag. Ag3 PO4 is reduced to Ag nanoparticles, which are dispersed on the nanosheet-built hierarchical Bi2 MoO6 nanoboxes. With the investigation of intermediate products, the growth process of Ag/Bi2 MoO6 is studied. Due to the hierarchical hollow structure and the introduction of Ag, the Ag/Bi2 MoO6 nanoboxes exhibit enhanced visible-light absorption and photocatalytic performance compared to the pristine Bi2 MoO6 microboxes.